2017
DOI: 10.1002/jrs.5253
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational properties of layered BiTeCl single crystal

Abstract: Bismuth tellurohalides have intrigued numerous interests for their novel Rashba splitting electronic structures with potential applications in spintronics and two‐dimensional (2D) optoelectronics. In this work, we have a detailed study of bulk BiTeCl and its exfoliated flakes using ultralow wavenumber Raman spectroscopy. We observe all BiTeCl characteristic Raman modes including the lowest wavenumber rigid layer in‐plane vibrational mode E32 at 19 cm−1. From 77 to 300 K, hardening of Raman modes are observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In another experimental study, it has been reported that the BiTeCl is a semiconductor with an electronic band gap of 0.77 eV at room temperature, which makes it a suitable material for infrared detector and sensing applications [34,35]. The vibrational properties of bulk and exfoliated flakes of BiTeCl have been examined by Raman spectroscopy, providing basic information on lattice dynamics [36]. Furthermore, theoretical calculations and experimental analysis have demonstrated pressure-induced topological phase transitions and superconductivity in BiTeX crystals [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In another experimental study, it has been reported that the BiTeCl is a semiconductor with an electronic band gap of 0.77 eV at room temperature, which makes it a suitable material for infrared detector and sensing applications [34,35]. The vibrational properties of bulk and exfoliated flakes of BiTeCl have been examined by Raman spectroscopy, providing basic information on lattice dynamics [36]. Furthermore, theoretical calculations and experimental analysis have demonstrated pressure-induced topological phase transitions and superconductivity in BiTeX crystals [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The main strength of the Raman spectroscopy is able to provide a great wealth of molecular vibration information. [ 40,41 ] The experimental Raman spectra of benzofuroxan at the selected pressure in the spectral range of 400–1,700 cm −1 have been shown in Figure 2. It can be seen that there are about 15 Raman bands ( v 1 –v 15 ) that can be observed at ambient pressure.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the presence of BiTeCl sheets, we have used conventional nondestructive Raman spectroscopy. Previously, this method has been widely used to characterize bulk BiTeCl ,, as well as other Janus crystals with well-established Raman spectra. Vibrational representation of zone-center phonons of BiTeCl can be written as Γ = 2A 1 +3B 1 +2E 1 +2E 2 where all the modes should be observed except silent B 1 modes.…”
Section: Resultsmentioning
confidence: 99%